Pengaruh Green Marketing dan Brand Awareness Terhadap Keputusan Pembelian Konsumen Produk Merek Aqua - Salam, Abdul; Sukiman, Sukiman (Universitas muhammadiyah palembang, 2021)
This research aims to examine the effect of green marketing on purchasing decisions and the influence of brand awareness on purchasing decisions for Aqua branded Bottled Drinking Water (AMDK) products. The variables used in this study are Green Marketing and Brand Awareness as an independent variable, and purchasing decisions as the dependent variable. This research uses quantitative methods. The number of samples used in this study were 100 respondents. By taking the sample using nonprobability sampling method with purposive sampling technique.The data collection method used a questionnaire. This study uses multiple linear regression analysis techniques using analysis tools SPSS version 20.0 for windows. The results of the analysis in this study indicate that (1) the Green Marketing variable has a significant effect on purchasing decisions with a t value of 2.029, greater than t table 1.984 with a significant value of 0.045, less than 0.05. (2) Brand Awareness variable has a significant effect on purchasing decisions with a t count value of 8.431, greater than t table 1.984 with a significant value of 0.000, smaller 0.05.